Murcott (Honey Tangerine) - Stephen H. Futch; L.K. Jackson (EDIS)
The actual origin of the Murcott is unknown but is most likely a tangor, which is a cross between a tangerine and a sweet orange. The early history discusses the possibility that the variety originated in a USDA planting around 1916. In about 1922, early history states that Mr. Charles Murcott Smith had a nursery in Bayview, Pinellas County, Florida where several of these trees were located. Mr. Smith most likely obtained the original trees from the USDA. This document was first time published in 1993.